The Effectiveness of Using the Minnesota Model in Completing University Physics Selection Exam - Syukri, Muhammad; Putri, Elva Sesioria; Evendi, Evendi; Yusrizal, Yusrizal; Hamid, Abdul (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study raises the issue of whether the Minnesota model in solving university selection physics questions gets the right results in terms of answers and time. This research aims to determine the effectiveness of using the Minnesota problem-solving model for the accuracy of answers and time in solving physics problems. The type of research is quantitative research with experimental methods. The population of this study was students of class XI from senior high school in Banda Aceh. The sample in this study was two classes. There was the experimental class and control class. Determination of the sample is done by purposive sampling. The approach used is a quantitative approach with the type of experimental research. The data was collected using a written test technique and data processing using an analysis of the effectiveness of the accuracy of the answers using an assessment rubric that has been validated and using t-test statistics, as well as the effectiveness of the use of time analysis based on the average time use of the two classes. The results of the data analysis showed that the average value of the experimental class using the Minnesota problem-solving model was higher than the control class, and the experimental class’s time usage was faster than the control class. It was stated that the Minnesota problem-solving model was effectively used in solving physics problems.